Comparison of numerically-analytical and finite-element solutions of the Lame problem for nonlinear-elastic cylinder under large strains. Issue 4 (February 2019) - Zingerman, K M; Vershinin, A V; Levin, V A
Abstract: The results of a comparison of the numerical-analytical solution of the Lame problem for a cylinder made of nonlinear elastic material with the solution of the same problem by the finite element method are presented. Calculations are made for the compressible Mooney-Rivlin material and the Murnaghan material. The numerical-analytical solution is based on the use of the semi-inverse method, which is briefly described in relation to the class of problems under consideration; the problem reduces to solving the Cauchy problem for an ordinary differential equation. A finite-element solution was found in a three-dimensional formulation using the Fidesys engineering strength analysis system using 8-node and 20-node elements. The influence of the type of finite elements, material parameters and the magnitude of the applied load on the computational error is investigated.